A methods engineering study on Lamoiyan Corporation - Cordova, Kenneth Irving; Fabillar, Rosaly Anne; Tantay, Costa Palma; Telan, Romina (College of Engineering, 2002)
Lamoiyan Corporation has been the first Filipino toothpaste manufacturer. The study was focused on the high percent yield in the number of rejects in the toothpaste production. There were three areas of concern that were analyzed since the results showed that these were the most problematic. These were : breakage and improper sealing of toothpaste tubes by the machines, breakage of toothpaste tubes after passing through the machines, and from the large amount of scrap produced from damaged and unaligned toothpaste tubes. The root causes of these problems were identified and analyzed. There were eight problems identified and verified. Alternatives were generated and evaluated in order to address the verified problems. There were five alternatives chosen to improve the current system of the company and to address the problems currently faced by the company. The improvements proposed were : 1) Revision of Machine Maintenance Schedule 2) Proper Inspection 3) Implementation of Regular Machine Maintenance Schedule 4) Installation of Additional Machines and lastly, 5) Bigger Tables and More Workers. Implementation of Alternatives are discussed in detail. A separate section called AREAS FOR FURTHER STUDY was included to list some of the areas of concern that might investigate interest and future stuffy and research.